A Method for Quantifying Automobile Brake Creep Groan Intensity Based on Friction-Induced Vibration and Noise - Lijun Zhang; Jianfeng Wu; Dejian Meng (Shock and Vibration)
To quantify the intensity of automobile brake creep groan, both experimental and analytical studies are innovatively conducted on the friction-induced vibration and noise of the disc brake in this paper. Experimentally, three factors, brake disc initial temperature, terrain, and gear position, are comprehensively contemplated to design six different test conditions, based on which a creep groan vehicle road test is conducted. Depending on the subjective evaluation and statistical analysis of the annoyance degree caused by vibration and noise in the starting and braking process under different test conditions, the influence of each factor on creep groan intensity is obtained. By processing the brake caliper and lower suspension arm acceleration and the interior sound pressure signals acquired in the test, the occurrence conditions and transient dynamic characteristics of creep groan are explored. One of the creep groan vibration modes is triggered by the rapid removal of the force exerted on the brake pedal when the vehicle starts at an extremely low speed, which presents intermittent impact and chaotic characteristics. The other vibration mode shows periodic harmonic characteristics, whose energy is concentrated on specific frequencies in the form of frequency doubling. This vibration mode occurs when continuously maintaining a low brake oil pressure or slowly releasing the force exerted on the brake pedal during the vehicle low-speed starting process, the velocity-displacement phase-plane portrait of which shows a stable limit cycle of stick-slip motion. Analytically, four vibration indexes and four noise indexes are established to evaluate the intensity of creep groan, the validity of which is verified by linear regression analysis. Finally, by combining all effective indexes, multiple linear regression analysis is performed, based on which the mapping relationship between the subjective evaluation of creep groan and effective indexes is obtained. The results demonstrate that the combination of the logarithmic vibration dose value of maximum brake caliper acceleration pulse and the loudness of interior noise can accurately describe the annoying degree caused by creep groan. The regression model can quantify and predict creep groan intensity of the test vehicle under different test conditions, which has guiding significance for engineering applications.